2004
DOI: 10.1051/rnd:2004061
|View full text |Cite
|
Sign up to set email alerts
|

The differential requirement of albumin and sodium citrate on the development of in vitro produced bovine embryos

Abstract: -In vitro culture for bovine embryos is largely not optimal. Our study was to determine the components necessary for early embryo development. In experiment 1, IVF embryos were cultured for two days in CR1aa medium containing sodium citrate and BSA from two sources (Sigma vs. ICPbio), subsequently for additional five days with cumulus monolayer in 10% FBS CR1aa. We found that supplementation with both Sigma-BSA and sodium citrate significantly increased total blastocyst (BL) development compared with the ICPbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
0
9
0
2
Order By: Relevance
“…It is known that citrate does not seem to improve sperm motility after freezing [11]. Addition of citrate to bovine embryo culture appears to enhance morula and blastocyst development, and hatching [12][13][14], although in one study no impact on bovine blastocyst formation was found [15]. The present results indicate that it could be beneficial for early human embryo development to have citrate in the fertilization medium.…”
Section: Discussionmentioning
confidence: 46%
“…It is known that citrate does not seem to improve sperm motility after freezing [11]. Addition of citrate to bovine embryo culture appears to enhance morula and blastocyst development, and hatching [12][13][14], although in one study no impact on bovine blastocyst formation was found [15]. The present results indicate that it could be beneficial for early human embryo development to have citrate in the fertilization medium.…”
Section: Discussionmentioning
confidence: 46%
“…Um efeito benéfico do citrato também pode ser pela presença de células somáticas no cultivo, como realizado no presente trabalho. Sung et al (2004) observaram efeito positivo no desenvolvimento embrionário quando utilizaram citrato durante cocultura, sugerindo que este pode atuar removendo potenciais metabólitos tóxicos secretados por células somáticas. Células do cumulus têm papel antioxidativo no cultivo de oócitos suínos (Tatemoto et al, 2000) e na fertilização em bovinos (Fatehi et al, 2005).…”
Section: Resultsunclassified
“…O uso do citrato no desenvolvimento embrionário tem sido avaliado em meio fluido sintético do oviduto (SOF), estimulando a produção de embriões (Holm et al, 1999), sendo atualmente incorporado à sua composição. O meio SOF suplementado com citrato é amplamente utilizado em ambiente atmosférico com 5% de O 2 (Holm et al, 1999;Sung et al, 2004), contudo, em ambiente com maior concentração de oxigênio (ar atmosférico; 20% de O 2 ) e na ausência de células somáticas, pode resultar em baixo desenvolvimento embrionário (Rizos et al, 2001). O uso do citrato em outras condições de cultivo não tem sido avaliado.…”
unclassified
“…Despite the advantages of using BSA and FCS in embryo media, their composition is not stable and varies between batches. They contain vitamins, growth factors, amino acids, energy substrate, and minerals, and they are known to exhibit a variable ability to support blastocyst development in culture [ 63 , 67 ]. The literature does not allow us to conclude whether EG or GLY protocol is more effective since there are no/few pregnancy data available [ 57 ] and the studies comparing the EG and GLY protocols do not show any significant difference [ 68 , 69 ] in survival and hatching rates.…”
Section: Discussionmentioning
confidence: 99%